Agricultural radio talks and drama: Malaysia early development experience - Fadzilah Yusof,; Faridah Ibrahim,; Wan Amizah, WM (Universiti Kebangsaan Malaysian, 2012)
Agricultural broadcast has played a vital role towards Malaysian agricultural development. The article discusses the use of radio talks and dramas in developing the agricultural industry in Malaysia. The study applied qualitative method, namely document analysis, in-depth interview and content analysis of radio dramas such as Kebun Pak Awang (Pak Awang’s Garden) and Kemajuan Kampung (Village’s Progress). The study found that in the early years, agricultural extension services are limited through agricultural agencies which serve the needs of colonials on commodity plantation such as rubber, cocoa and pepper. Government development plans and strategies were inserted within the radio drama, talk or entertainments to gain peoples interest and collaboration. After the independence of Malaysia the agencies responsibilities were widen to help rural peasants to improve their yields by using technologies and new breeds in their fields.